(Not)Knowing: Walking the Terrain of Indigenous Education with Preservice Teachers - McDowall, Ailie (The Australian Journal of Indigenous Education, 2017)
Our work as educators is entangled in questions of how colonisation privileges particular epistemologies and ontologies, ethical responsibilities and the reproduction of privilege or exclusion through education. Working with preservice teachers as they shape their social and ethical responsibilities allows the opportunity to effect social change on a larger scale as they move into their own classrooms. Students often begin the course seeking some form of knowledge about Indigenous peoples, yet this knowledge can be seen to represent a form of epistemic violence. In this research project, I use a decolonial lens to consider the reflective writing journals of preservice teachers as they consider their relationships and responsibilities in the field of Indigenous education. The purpose is to explore how preservice teachers position themselves in this field and whether their engagement with these stories, theories, voices and knowledges leaves them with an inability to remain indifferent to their ethical responsibilities. In this paper, I invite you to walk with me through a landscape where we consider preservice teachers’ writings, Moreton–Robinson's possessive logic, transformative education and the concept of diffraction.